2016
DOI: 10.2355/isijinternational.isijint-2015-538
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Flow and Crystallization Behaviors of P-bearing Steelmaking Slags with Varying Fluorine Content

Abstract: The role of fluorine in the CaO-SiO 2 -MgO-Al 2 O 3 -Fe t O steelmaking slags was investigated through analyzing the viscous flow and crystallization behaviors of the slags. It was found that the viscosity decreased with increasing CaF 2 content, which resulted from the decrease of the degree of polymerization (DOP) of the structures, as proved by O 1s X-ray photoelectron spectroscopy (XPS) and magic angular spinning nuclear magnetic resonance (MAS-NMR) analysis. The continuous cooling transformation (CCT) dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
1
3
0
1
Order By: Relevance
“…The high‐frequency region corresponded to the [SiO 4 ]‐tetrahedral units with varying amounts of oxygen anions. Similar results have been obtained for silicate slags . The peaks shifted toward higher frequencies with an increase in BaO content, suggesting an increase in the DOP of the slag system.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The high‐frequency region corresponded to the [SiO 4 ]‐tetrahedral units with varying amounts of oxygen anions. Similar results have been obtained for silicate slags . The peaks shifted toward higher frequencies with an increase in BaO content, suggesting an increase in the DOP of the slag system.…”
Section: Resultssupporting
confidence: 85%
“…Similar results have been obtained for silicate slags. 11,[30][31][32] The peaks shifted toward higher frequencies with an increase in BaO content, suggesting an increase in the DOP of the slag system. In the low-frequency region, the peak at about 480 cm À1 corresponding to the Si-O-Al stretching vibrations became pronounced with an increase in the BaO content.…”
Section: Analysis Of the Effect Of Bao Substitution On The Structurmentioning
confidence: 99%
“…Lockyer [10] pointed out that Ca 2+ preferred to associate with than with silicate species for the greater stability of P–O–M (M is cation) than of Si–O–M in the Na 2 O–CaO–SiO 2 –P 2 O 5 system, which results that an increasing P 2 O 5 addition captured more than the NBO of the [SiO 4 ]-tetrahedra and brought about the degree of polymerization of molten slag rising. Wang et al [11] showed that the addition of CaF 2 reduced the degree of polymerization of P-bearing steelmaking slags because F ions mainly coordinated with Ca 2+ ions to form Ca–F bond. And the presence of Ca–F bonds (Si–O–Ca–F) and the greater stability of P–O–Ca than that of Si–O–Ca bonds could work together to promote the formation of Si–O–Ca–F and thus the primary crystal variation from spinel (MgFe 2 O 4 ) to fluorapatite phase (Ca 5 (PO 4 ) 3 F) with the addition of CaF 2 , which was beneficial to the further study of dephosphorization process and enrichment of phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these investigations, various studies have been explored to reveal how to boost the phosphorus content in nC2S-C3P solid solution through adding different additives in the complex CaO-SiO2-MgO-Al2O3-FetO-P2O5 multiphase. [9,[18][19][20][21] A series of studies have been carried out to explore the P concentrating phase in steelmaking slags modified by Fe2O3, P2O5, Al2O3 and CaF2 additives, [22][23][24][25] where the essential structure of the slags has been systematically studied, especially Fe 3+ , P 5+ , Al 3+ and F -. Meanwhile, some other studies about the structure also replenished the investigation of the slags.…”
Section: Introductionmentioning
confidence: 99%